2014
DOI: 10.4137/ccrpm.s16760
|View full text |Cite
|
Sign up to set email alerts
|

Improved Arterial Blood Oxygenation following Intravenous Infusion of Cold Supersaturated Dissolved Oxygen Solution

Abstract: BACKGROUNDOne of the primary goals of critical care medicine is to support adequate gas exchange without iatrogenic sequelae. An emerging method of delivering supplemental oxygen is intravenously rather than via the traditional inhalation route. The objective of this study was to evaluate the gas-exchange effects of infusing cold intravenous (IV) fluids containing very high partial pressures of dissolved oxygen (>760 mm Hg) in a porcine model.METHODSJuvenile swines were anesthetized and mechanically ventilated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Therefore, this method should be studied in vivo model of hypoxemia. A previous study on juvenile swine demonstrated a significant increase in the pO 2 from 78 to 94 mmHg 1 h after the injection of a cold supersaturated oxygen solution (at a pO 2 : 992 mmHg) administered by an IV infusion [14]. The mean body weight of the animals in that study was 12.9 kg, and the IV infusion volume was calculated to be 390 mL per hour, although the IV flow rate in that study was different from that of 1200 mL per hour used in our present study.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, this method should be studied in vivo model of hypoxemia. A previous study on juvenile swine demonstrated a significant increase in the pO 2 from 78 to 94 mmHg 1 h after the injection of a cold supersaturated oxygen solution (at a pO 2 : 992 mmHg) administered by an IV infusion [14]. The mean body weight of the animals in that study was 12.9 kg, and the IV infusion volume was calculated to be 390 mL per hour, although the IV flow rate in that study was different from that of 1200 mL per hour used in our present study.…”
Section: Discussionmentioning
confidence: 94%
“…Solubilization of oxygen gas in aqueous solutions plays an important role in the functioning of biological systems, as well as in various industrial processes. This includes oxygen supersaturated solutions where the concentration of oxygen exceeds equilibrium level. Their applications range from facilitation of the surface oxidation of silicon , in semiconductor industries to various treatments in medicine, including therapeutic oxygen for hypoxia, oxygenation of arterial blood, wound healing, and stimulation of immune activity. Oxygen supersaturated solutions can be produced through physical agitation in combination with elevated partial pressure of oxygen or chemically. , In the second case, oxygen is formed directly from chemical reactions such as electrolysis of water or decomposition of hydrogen peroxide, 2H 2 O 2 → 2H 2 O + O 2 . The chemical production is utilized in a variety of industrial processes, especially because its speed can be controlled by adding catalysts such as catalase or iron .…”
Section: Introductionmentioning
confidence: 99%